1993
DOI: 10.1111/j.1423-0410.1993.tb02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anti‐Hepatitis C Virus in the Blood Donor Population of Rio de Janeiro

Abstract: The prevalence of hepatitis C virus (HCV) antibodies in 2,557 asymptomatic volunteer Brazilian blood donors is reported. Using the line immunoassay (Inno-LIA) as a confirmatory test on ELISA anti-HCV-positive reacting sera, a prevalence rate of 2.7% for anti-HCV positivity was found. By comparison, prevalences of 1.6% for hepatitis B surface antigen, 0.9% for Treponema pallidum, 0.4% for human immunodeficiency virus and 0.04% for Trypanosoma cruzi were observed. Only 57% of the HCV-positive donors had elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0
3

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
(8 reference statements)
3
8
0
3
Order By: Relevance
“…Rio de Janeiro is a region of low endemicity for HBV infection (<2% HBsAg prevalence) (17). The frequency of HBsAg found in this study (7.8%) is comparable with that observed in areas of high endemicity, with more than 8% of HBsAg prevalence, and agrees with results from other studies of IDUs in Santos, SP, Brazil (18), and in other countries (9).…”
Section: Discussionsupporting
confidence: 81%
“…Rio de Janeiro is a region of low endemicity for HBV infection (<2% HBsAg prevalence) (17). The frequency of HBsAg found in this study (7.8%) is comparable with that observed in areas of high endemicity, with more than 8% of HBsAg prevalence, and agrees with results from other studies of IDUs in Santos, SP, Brazil (18), and in other countries (9).…”
Section: Discussionsupporting
confidence: 81%
“…The overall prevalence of 2.5% for anti-HCV in this study was similar to those noted by Vanderborght et al (1993) in the city of Rio de Janeiro. We found a low rate (1.9%) of anti-HBc among blood donors anti-HCV positive and Vasconcelos et al (1994) found (2.7%).The importance of anti-HBc as an alternative HCV marker has been questioned following the introduction of sensitive HCV tests for the screening of donors (Barbara 1994, Dodd 1995.…”
supporting
confidence: 71%
“…Vasconcelos et al (1994) reported a significant correlation among anti-HBc positivity and elevated ALT levels. Vanderborght et al (1993) also reported an increasing reactivity for anti-HCV associated with ALT elevation. Concerning the NIH (1995) evaluation, the maintenance of ALT screening did not improve the transfusion safety even during the infection, prior to the appearance of anti-HCV.…”
mentioning
confidence: 99%
“…Rio de Janeiro, a state within Southeast region, has an overall hepatitis B surface antigen (HBsAg) prevalence about 2% in general population (Nogueira et al 1990, Vanderborght et al 1993 the virus by sexual route but risk factors for this way has not been properly evaluated. Screening for hepatitis B in sexual transmission diseases (STD) clinics is not considered as routine procedure.…”
Section: Hepatitis B Virus (Hbv) Has a Low Endemicity In Rio Dementioning
confidence: 99%